(untitled) (Linguostylistic Studies, 2015)
This article provides deliberate studying of the stylization method effectiveness in terms of practical author style mastering during the classes on stylistics. Exact definitions of the notions “author style” as well as “stylization” are given. “The author style” means a particular entity characterized with peculiarities of world perception, outlook and aesthetic taste of the author. Stylization is an exact, clear imitation of the original peculiarities of a particular style or the peculiarities of the speech of some exact surrounding, historical epoch in the artistic work. We consider that the exercises directed on writing stylizations of the works of different poets-representatives of world literature are helpful in developing creative potential of the students. They also contribute to better understanding of the material covered within the topic of author style learning. This article also deals with the advantages and risks of the stylization method usage during the classes on English stylistics. Key words: style, author style, stylization, the method of stylization, the problem of author style investigation. References